Reclassification of Excess Royalty Payments as Disguised Dividends in a Secondary Adjustment Framework Under Indonesian Tax Law and OECD Standards - Bangkit Cahyono; Zudan Arief Fakrulloh (International Journal of Social Service and Research, 2026)
The increasing complexity of cross-border controlled transactions conducted by multinational enterprises has created significant challenges in international taxation, particularly concerning transfer pricing practices and profit shifting through excessive royalty payments. Such payments may reduce taxable income in source jurisdictions and contribute to potential tax base erosion, requiring effective legal mechanisms to ensure equitable taxation. This study aimed to examine the legal basis, normative challenges, and compatibility of Indonesia’s secondary adjustment framework in reclassifying excessive royalty payments as deemed dividends under Indonesian tax law and OECD standards. This research employed a normative juridical method using statutory and conceptual approaches. Legal materials were collected from Indonesian tax regulations, including the Income Tax Law, Government Regulation Number 55 of 2022, Minister of Finance Regulation Number 172 of 2023, and international references, such as the OECD Transfer Pricing Guidelines. The findings indicated that Indonesia had established a legal foundation for secondary adjustments through the constructive dividend approach. However, several normative issues remained, particularly regarding the extension of the dividend concept to transactions involving non-shareholders, potential ultra vires interpretations, and the risk of international double taxation. The study concluded that Indonesia’s framework required further regulatory clarification and technical guidance to ensure consistency with OECD principles, strengthen legal certainty, and establish a fairer approach to resolving transfer pricing disputes involving excessive royalty payments.